The application of big data network crawler technology for architectural culture and environment protection. (13th April 2020) - Jian, Zhichao; Qin, Lichun
Summary: In today's big data environment, we get the Maonan residential information of Maonan Nationality in Huanjiang through the web crawler technology, and further study the protection and renewal of the local architectural culture and environment, in order to promote the social civilization and sustainable development. With the continuous development and improvement of Internet technology, information acquisition technology of Web crawler based on large data is particularly important. It can collect network information intelligently and efficiently. Taking the architectural protection as the research object, Maonan Ethnic Group in the area is chosen as the object of study. Based on the web crawler technology, the protection and development of the local residential architecture culture and environment are analyzed. Through data collection and investigation of big data crawler technology, we find that the Maonan Ethnic Group has unique local customs and cultural details. Therefore, how to carry out sustainable development according to the unique local cultural characteristics and by means of information technology will become the focus of further research.